2004
DOI: 10.1016/j.febslet.2004.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GSK3β by indirubins restores HIF‐1α accumulation under prolonged periods of hypoxia/anoxia

Abstract: Hypoxia inducible factor 1 is regulated by the appearance of the HIF-1a subunit. HIF-1a is subjected to proteasomal destruction or enhanced protein translation, which requires the phosphatidylinositol 3-kinase (PI3K)/Akt pathway. We investigated how PI3K/Akt and glycogen synthase kinase 3b (GSK3b) affect HIF-1a in human RKO cells under prolonged periods of severe hypoxia/anoxia. 16-to 32-h lasting incubations attenuated Akt activity and decreased HIF-1a protein. This was reproduced by blocking PI3K with LY2940… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 26 publications
4
31
0
Order By: Relevance
“…In contrast, activation of ERK1/2 did not affect HIF-1␣ mRNA levels. In line, several studies have identified the PI3K/AKT pathway as an important element in hypoxic induction of HIF-1␣ protein and activity (Kietzmann et al, 2003;Mottet et al, 2003a;Schnitzer et al, 2005;Lee et al, 2006). In addition, the PI3K pathway is also involved in the activation of NFB (Sizemore et al, 1999;Madrid et al, 2000), and in fact, inhibitors of PI3K but not of ERK1/2 prevented activation of NFB by hypoxia, indicating that PI3K/AKT activates HIF-1␣ indirectly by inducing NFB.…”
Section: Nfb Is Activated By Hypoxia and Mediates The Induction Of Himentioning
confidence: 72%
“…In contrast, activation of ERK1/2 did not affect HIF-1␣ mRNA levels. In line, several studies have identified the PI3K/AKT pathway as an important element in hypoxic induction of HIF-1␣ protein and activity (Kietzmann et al, 2003;Mottet et al, 2003a;Schnitzer et al, 2005;Lee et al, 2006). In addition, the PI3K pathway is also involved in the activation of NFB (Sizemore et al, 1999;Madrid et al, 2000), and in fact, inhibitors of PI3K but not of ERK1/2 prevented activation of NFB by hypoxia, indicating that PI3K/AKT activates HIF-1␣ indirectly by inducing NFB.…”
Section: Nfb Is Activated By Hypoxia and Mediates The Induction Of Himentioning
confidence: 72%
“…52 Interestingly, hypoxic conditions were shown to inhibit the activity of the PI3K pathway, in an experimental system similar to that where the effect of hypoxia on p53 was described. 53,54 Thus, the molecular mechanisms underlying stabilization of the p53 protein overlap only partially with those controlling its activation as a transcriptional activator. In this regard, the precise roles of specific post-translational modifications or coactivators may be cell-type and cell-context dependent.…”
Section: Discussionmentioning
confidence: 99%
“…The AKT/GSK3 signaling pathway regulates HIF-1␣ protein stability (11,50). Inhibition of GSK3␤ activation by LiCl or overexpression of dominant negative GSK3␤ mutant is known to increase of HIF-1␣ expression and activity (52,53). Furthermore, various reports show that the transcription factor Snail is regulated by growth factors or integrins (6 -8).…”
Section: Discussionmentioning
confidence: 99%